Automatic control of structural parts main parameters during mechanical testing of aircraft - Simonov, V L; Yu Eliseeva, D; Mnatsakanyan, O L; Karyagina, T V (IOP conference series. Materials Science and Engineering, 2020)
In the aviation industry over the past few years, much work has been done to improve the conditions for the design, manufacture of aircraft, as well as their operation. New models of Russian aircraft are not inferior, and sometimes surpass foreign analogues in a number of parameters. At the same time, flight safety requirements are growing. The introduction of digital innovation is dictated by the growing requirements for technological innovation in the aviation industry. The world is on the verge of a new, fourth industrial revolution, Industry 4.0, whose large-scale penetration will lead to the complete automation of most production processes. Domestic production of various types of aircrafts for civilian and military purposes should reach a new level of technological development in order to protect its role in global economic competition. In this regard, the volume of research, design and development, installation and commissioning, testing and service-maintenance work is significantly increasing. It is possible to achieve an increase in the quality of flight performance and the level of flight safety of an aircraft by creating an automatic system for monitoring the main parameters of structural parts during mechanical tests of aircraft. This article is devoted to the study of automation of control of parameters of structural parts during mechanical tests of aircraft, the process of development and testing of an automated complex for vibration testing of parameters of structural parts of aircraft is considered.